3x + 8
Combine like terms. 6x - 2y +7.
To solve the equation 6x plus 4-3x,first subtract 3x from 4 which leaves you with 1x. The equation now reads 6x plus 1x, which equals 7x. --- Actually, to simplify this, we have to keep the numbers multiplied with the variables from the plain numbers. The equation based on the question it this: 6X + 4 - 3X So there is a +6X a -3x and a +4. So we simplify by consolidating the numbers multiplied with the Xs. So 6X - 3X is 3X. So we have 3x + 4. There is no way to solve this since we have only part of it and no equal sign.
3x + 6x - x= 8x
3x + 6y + 6x = 9x + 6y which can be factorised as 3(3x +2y)
If that's 6x + 10, that factors to 2(3x + 5)
6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...
That simplifies to 3x - 9y. It can't be solved since it doesn't equal anything.